2022
DOI: 10.3390/healthcare10030464
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an Antimicrobial Stewardship Programme to Improve Adherence to a Perioperative Prophylaxis Guideline

Abstract: Perioperative antimicrobial prophylaxis is effective in reducing the rate of surgical site infections (SSIs); however, non-adherence to surgical antimicrobial prophylaxis protocols can lead to several negative outcomes. We performed a before-and-after intervention study with the aim of improving the process outcome, including adherence to guidelines. Another objective of this study was to investigate improvement in patient outcomes as a result of adherence to a surgical antimicrobial prophylaxis programme. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The presence of an effective hospital antimicrobial stewardship program could be attributed to the successful implementation of guidelines and antibiotics policies, in addition to the quality improvement initiative projects conducted by ASP core members. This is in line with multiple recent studies (15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 93%
“…The presence of an effective hospital antimicrobial stewardship program could be attributed to the successful implementation of guidelines and antibiotics policies, in addition to the quality improvement initiative projects conducted by ASP core members. This is in line with multiple recent studies (15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 93%
“…Other studies conducted in Malaysia and Pakistan showed that community pharmacists agreed with the importance of AMS to improve patient care [16,18]. However, another study in Saudi Arabia indicated that the lack of internal policies and procedures and inadequate training were the biggest obstacles for AMS [22]. This study reported that most of the pharmacists agreed that AMS should be focused on the communitypharmacy level, and they also agreed that adequate training on antibiotics use and attending programs to improve understanding of AMS are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that 82.40% of surgical patients were given prophylactic antibiotics of different types; the most widely used antibiotics were ceftriaxone at 28.44%, metronidazole at 26.36% and the rest were other types of antibiotics [21].…”
Section: Figure 1 Number Of Publications By Yearmentioning
confidence: 99%